2016
DOI: 10.1007/s11427-016-0357-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced CD69+ Kupffer cell feedback inhibits T cell proliferation via membrane-bound TGF-β1

Abstract: Kupffer cells, the bone marrow-derived population. Hepatic CD69 + Kupffer cells suppressed Ag-nonspecific and OVA-specific CD4 T cell proliferation through mTGF-β1 both in vitro and in vivo, meanwhile, they did not interfere with activation of CD4 T cells. Thus, we have identified a new subset of inflammation-induced CD69 + Kupffer cells which can feedback inhibit CD4 T cell response via cell surface TGF-β1 at the late stage of immune response against infection. CD69 + Kupffer cells may contribute to protect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…In addition, TGF-β1 has a negative regulatory role in the immune function of mice. The results of the present study are similar to those reported previously (59). IL-17A is a recognized inflammatory factor, and there was no significance difference in IL-17A levels among the groups.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, TGF-β1 has a negative regulatory role in the immune function of mice. The results of the present study are similar to those reported previously (59). IL-17A is a recognized inflammatory factor, and there was no significance difference in IL-17A levels among the groups.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, only mitotane alone or combined with EF24 decreased the reactivity of Erk1/2 and Akt. Of note, phospho-NF-κB was augmented by EF24 at 5 h in both cell lines and at 72 h in H295R cells (Figure 7A,B); similar results have already been reported, underlining that small doses of curcumin could enhance proliferation and survival [23,24] and could possibly potentiate cell death by DNA damage or oxidative stress [25,26,27]. On the same line, we showed an increase in phosphorylation of Erk1/2 at 5 h in SW13 cells (by EF24 alone or combined), suggesting that under certain circumstances, Erk1/2 can have pro-apoptotic functions, as it is the most important balance between pro- and anti-proliferative signals (Figure 3 and Figure S1), which was already reported by Thomas et al in 2010, where EF24 was shown to significantly induce the upregulation of Erk1/2, JNK, and p38 (MAPK pathway) [20,28,29].…”
Section: Discussionsupporting
confidence: 82%
“…The positive correlation between C1QA and CD68 and the negative relationship between MARCKSL1 and N4BP2L2 are novel findings in STAD research. In lung cancer, CD68 has been associated with tumour‐associated macrophages and linked to poor prognosis, 34 but its relationship with C1QA in STAD suggests a unique immune modulation. Comparatively, the negative interaction of MARCKSL1 and N4BP2L2 is a relatively unexplored area and could be pivotal in understanding the immune evasion mechanisms in STAD.…”
Section: Discussionmentioning
confidence: 99%